2020
DOI: 10.11628/ksppe.2020.23.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Horticultural Activities in the Teacher’s Guidebooks of Nuri Curriculum for 5-Year-Olds

Abstract: The purpose of this study was to analyze the frequency and contents of horticultural activities in 696 individual activities listed in 11 teacher's guidebooks of Nuri Curriculum for 5-year-olds, and to find out the perceptions of horticultural activities in the formal curriculum. The target horticultural activities that were selected were those using natural objects like potted plants, water, wind, soil, stones, etc. as the topic or subject of activities, and those with different topics but are mentioning plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Meanwhile, as a result of analyzing the frequency and content of horticultural activities using 696 activities in 11 teacher's guidebooks for the 5-year-old Nuri Curriculum, it was found that the activities were concentrated on certain life topics mediated by video clips and photos and images of plants rather than real ones based on science, or merely talking indoors in big and small groups, which shows the lack of horticultural activities in the regular curriculum for early childhood (Choi et al, 2020). As suggested by the report that preservice early childhood teachers could overcome the difficulties as a teacher and gain confidence by developing and teaching the 'Forest Character Program' in association with a daycare center that is an institution of industry-education cooperation (Kang, 2016), horticultural activities perceived and experienced by early childhood teachers are important, but there is insufficient research on activities preferred by early childhood teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, as a result of analyzing the frequency and content of horticultural activities using 696 activities in 11 teacher's guidebooks for the 5-year-old Nuri Curriculum, it was found that the activities were concentrated on certain life topics mediated by video clips and photos and images of plants rather than real ones based on science, or merely talking indoors in big and small groups, which shows the lack of horticultural activities in the regular curriculum for early childhood (Choi et al, 2020). As suggested by the report that preservice early childhood teachers could overcome the difficulties as a teacher and gain confidence by developing and teaching the 'Forest Character Program' in association with a daycare center that is an institution of industry-education cooperation (Kang, 2016), horticultural activities perceived and experienced by early childhood teachers are important, but there is insufficient research on activities preferred by early childhood teachers.…”
Section: Introductionmentioning
confidence: 99%